Protection Coordination Practice in Electrical Substation Part-1 Overcurrent and Earth Fault Protection - Case Study of Siddik Kardesler Substation (SKS), Istanbul, Turkey - Shobole, Abdulfetah; Baysal, Mustafa; Wadi, Mohammed; Tur, Mehmet Rida (GAZI UNIV, 2017)
Protection coordination is the heart of all power systems. To ensure a quality and reliable operation of the power systems, an electrical fault must be cleared within a short time. This can be achieved by proper coordination between the protection relays. In Siddik Kardesler Substation the MV voltage feeders' protection is provided by overcurrent relays. This paper is principally concerned with practical protection coordination of the electrical substation by using Siddik Kardesler Substation substation as a case study. In the Part-2, distance and differential protection will be discussed. Finally, after test and commissioning, the substation is successfully energized without a problem.
Keywords: Earth Fault Protection; Over Current Protection; Protection Coordination; Electrical Substation; DIRECTIONAL OVERCURRENT; ALGORITHM; MALAYSIA; RELAYS; SYSTEM; Science & Technology - Other Topics